RhoE is regulated by cyclic AMP and promotes fusion of human BeWo choriocarcinoma cells. - Gavin P Collett; Xue Fang Goh; Elizabeth A Linton; Christopher W G Redman; Ian L Sargent (PLoS ONE)
Fusion of placental villous cytotrophoblasts with the overlying syncytiotrophoblast is essential for the maintenance of successful pregnancy, and disturbances in this process have been implicated in pathological conditions such as pre-eclampsia and intra-uterine growth retardation. In this study we examined the role of the Rho GTPase family member RhoE in trophoblast differentiation and fusion using the BeWo choriocarcinoma cell line, a model of villous cytotrophoblast fusion. Treatment of BeWo cells with the cell permeable cyclic AMP analogue dibutyryl cyclic AMP (dbcAMP) resulted in a strong upregulation of RhoE at 24 h, coinciding with the onset of fusion. Using the protein kinase A (PKA)-specific cAMP analogue N(6)-phenyl-cAMP, and a specific inhibitor of PKA (14-22 amide, PKI), we found that upregulation of RhoE by cAMP was mediated through activation of PKA signalling. Silencing of RhoE expression by RNA interference resulted in a significant decrease in dbcAMP-induced fusion. However, expression of differentiation markers human chorionic gonadotrophin and placental alkaline phosphatase was unaffected by RhoE silencing. Finally, we found that RhoE upregulation by dbcAMP was significantly reduced under hypoxic conditions in which cell fusion is impaired. These results show that induction of RhoE by cAMP is mediated through PKA and promotes BeWo cell fusion but has no effect on functional differentiation, supporting evidence that these two processes may be controlled by separate or diverging pathways.